Maripousar: linhas e rotas da investigação de uma poética mestiça biomitográfica - Bruni Emanuele Fernandes (2022)
This dissertation is a body-text presented as a first outcome, a first act of elaboration that I have called Maripousar, a mestizo biomythographic poetics. Throughout the work, I trace some lines, sew together some routes covered conceptually and poetically throughout my research-creation. From the congregation and schematization of plastic and epistemological references – above all, although not only, the aesthetic confabulations and writings of Gloria Anzaldúa, Audre Lorde, bell hooks, Lélia Gonzalez, Jota Mombaça, Ana Raylander, Angélica Dass –, a critical and conceptual plot about what is understood as emerging anti-racist aesthetic confabulations in the context of an Amefrican mestizo consciousness in contemporary arts. I present the persona that I have incorporated, La Mariposa, in multiple performative gestures, which have been being manipulated for almost three years. Finally, as a result of this biomythographic mixed-poetics, my first essay for a book-performance Casulo-segredo, conceived and constructed from my creative research, is presented as an authorial plastic production.